Synthesis of C37‐Alkenones for Past Climate Reconstructions. Issue 24 (20th March 2020) - Berton, Giacomo; Pizzini, Sarah; Fabris, Fabrizio; Bertolin, Tommaso; Pafumi, Eugenia; Ceccon, Leonardo; Daelemans, Jonas; Borsato, Giuseppe; Scarso, Alessandro; Piazza, Rossano; Ferretti, Patrizia
Abstract : The total syntheses of three C37 methyl‐alkenones with different degrees of unsaturation and of their 13 C‐labelled analogues from commercially available starting materials are presented herein for the first time. These molecules are important to improve the reliability of the measurements and reconstructions of the sea surface temperature and salinity. Abstract : The total syntheses of three C37 methyl‐alkenones with different degrees of unsaturation and their 13 C‐labelled analogues are presented herein. The products are important to improve the reliability of the measurements and estimations of the temperature and salinity of the oceans during the Cenozoic Era.